Breast Cancer Knowledge, Beliefs, and Screening Behaviors of College Women: Application of the Health Belief Model. Issue 4 (4th July 2017) - Guilford, Kendra; McKinley, Erin; Turner, Lori
ABSTRACT: Background : Breast cancer, the second leading cause of cancer death among US women, causes severe physiological problems, including treatment outcomes of surgery, radiation, and chemotherapy. It results in severe psychological suffering, including anxiety, depression, and disfigurement. One out of every 8 American women will develop breast cancer at some point in her life. Young women with breast cancer tend to experience more aggressive forms of the disease and with more severe outcomes than older women who develop breast cancer. Early detection and treatment are recommended for reducing mortality and suffering; however, screening behaviors are often avoided.Purpose : The purpose of this study was to examine breast cancer knowledge, beliefs, and screening behaviors among college women utilizing the health belief model.Methods : Participants completed a valid and reliable 84-item questionnaire that measured breast cancer knowledge, health motivation, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and breast self-examination practices among a sample of college women in the southeastern United States.Results : Participants ( n = 342) had low levels of breast cancer perceived susceptibility and breast self-examination. Breast cancer knowledge was significantly correlated with breast self-exam. In a regression model, positive self-efficacy and low perceive barriers were associated with breast self-examination.Translation to Health Education Practice : Health education program planners can enhance intervention effectiveness by utilizing health behavior constructs focused on increasing perceived susceptibility, enhancing self-efficacy for breast cancer screening, and reducing barriers. Education-based programs are also needed to increase women's overall knowledge and awareness of breast cancer.